The Lotus Sutra: A Biography, by Donald S. Lopez, Jr. - Prude, M. Alyson (Religions of South Asia, 2018)
The Lotus Sutra: A Biography, by Donald S. Lopez, Jr. Princeton, NJ: Princeton University Press, 2016. 257 pp., $29.95 (hb). ISBN 978-0-691-15220-2